2023
DOI: 10.4102/safp.v65i1.5553
|View full text |Cite
|
Sign up to set email alerts
|

The profile of Black South African men diagnosed with prostate cancer in the Free State, South Africa

Abstract: Background: Prostate cancer (PCa) ranks high in terms of morbidity and mortality, especially in Africa. Prostate-specific antigen (PSA) screening remains a practical method of screening for and thereby detecting PCa early, especially among African men who are more negatively affected. Modifiable risk factors for PCa are mostly behavioural and lifestyle. Understanding community-specific determinants is important when developing health promotion interventions.Objective: This study aimed to determine the profile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Other than the genetic factors, an explanation for this association is that reportedly, only 9.9% of Black South Africans have private health insurance and are therefore reliant on often over-crowded and under-resourced public healthcare services; while 72.9% of Europeans, 52% of Indians and 17.1% of South African Coloured report having private health insurance 22 . Additionally, a recent study in South Africa of 341 PCa cases reported that only 76 (22.3%) had awareness of PCa before diagnosis, with less than 50% of cases seeking medical help after PCa diagnosis 23 , and as such we call for further programs focused on bringing education and awareness across the region.…”
Section: Discussionmentioning
confidence: 94%
“…Other than the genetic factors, an explanation for this association is that reportedly, only 9.9% of Black South Africans have private health insurance and are therefore reliant on often over-crowded and under-resourced public healthcare services; while 72.9% of Europeans, 52% of Indians and 17.1% of South African Coloured report having private health insurance 22 . Additionally, a recent study in South Africa of 341 PCa cases reported that only 76 (22.3%) had awareness of PCa before diagnosis, with less than 50% of cases seeking medical help after PCa diagnosis 23 , and as such we call for further programs focused on bringing education and awareness across the region.…”
Section: Discussionmentioning
confidence: 94%
“…Other than the genetic factors, an explanation for this association is that reportedly, only 9.9% of Black South Africans have private health insurance, and are therefore reliant on often over-crowded and under-resourced public healthcare services; while 72.9% of Europeans, 52% of Indians and 17.1% of South African Coloured report having private health insurance 28 . Additionally, a recent study in South Africa of 341 PCa cases reported that only 76 (22.3%) had awareness of PCa before diagnosis and less than 50% of the cases sought medical help after being diagnosed 29 , and as such we call for further programs focused on bringing education and awareness across the region.…”
Section: Discussionmentioning
confidence: 96%
“…The authors have had to strike a balance and make recommendations applicable to both a well-resourced private sector and an under-resourced public sector. Epidemiological data showing the burden of disease, especially the rates of advanced disease in the coloured and black SA populations, [3,4,[37][38][39][40] suggest that a national PCa screening programme will be worthwhile; however, multiple factors make the roll-out of such a campaign particularly complex. Various studies have reported on the barriers to PCa screening in Africa, which include lack of patient education, poor uptake in low socioeconomic communities, and lack of resources to implement screening as well as treatment.…”
Section: Discussionmentioning
confidence: 99%